Study of modern pasture landscapes in subtropical zones of the Azerbaijan Republic - Maharram, Sultan Huseynova; Jafar, Shalala Salimova; Israphil, Gunay Mammadova; Musa, Ali Jafarov; Allahverdi, Turkan Hasanova; Ikhtiyar, Anara Nasirova; Nazim, Roza Mammadova; Ali, Ramil Sadigov; Gudrat, Vusala Isagova; Novruz, Lala Bunyatova (ECOTON: Ecological Observation and Wetlands Conservation, 2025)
The article shows climate data, soil moisture, humus and nitrogen content and other key indicators of the area (2022-2024). In this study we compare changes in the physicochemical properties of soils, the erosion factor, and humus and nitrogen reserves in natural ecosystems. The study of the variable importance of some soil parameters of forest ecosystems is considered relevant for Azerbaijani scientists. The highest erosion index was found in cultivated lands (0.270) and the lowest in protected forests (0.210). The results of this study showed that firewood cutting in natural forests, together with overgrazing, and forest to cultivated land conversion have caused significant soil degradation in the semi-arid region of Lerik. Overgrazing and exploitation of forest stands in natural forests, as well as the replacement of forests with cultivated lands, have significantly increased the density of sand (by 10.3-60.5%) and bulk density (4.1-7.16%), and have also significantly reduced the content of silt (2.34-8.56%), clay (2.36-10.5%), K (35.68-49.63%), P (15.58-29.38%), N (23.2-55.6%), and C (23.3-52.6%). There is little and rather contradictory information on the impact of grazing on soil properties. Research aimed at improving the use of pastures for grazing livestock in subtropical regions. No reliable changes in yield were found either at low grazing intensity (1/5, 1/10, 2/5) or at acceptable load levels (1/15, 2/10, 3/5) (13.7-14.6 t/ha). Grazing options 2/15, 3/10, 3/15 are excessive, leading to a decrease in yield by 0.43-3.07 t/ha, or 3.26-23.66%.